UPBRINGING YOUTH IN THE SPIRIT OF MILITARY-PATRIOTISM - Abdumumin Usmanov (Bright Mind Publishing, 2025)
This article analyzes the importance, methods, and results of educating youth in the spirit of military patriotism. During the study, an analysis of the literature, surveys, and observations were conducted. The results show that it is necessary to carry out systematic work in preschool, school, and higher educational institutions to educate young people in the spirit of patriotism. In conclusion, a comprehensive approach to youth education plays an important role in ensuring the development and security of our country.
Keywords: Military-patriotic education, youth, educational institutions, national values, defense of the Motherland.